Protected areas versus areas occupied by productive activities and infrastructure in Brazil – is there room for everybody? - Drummond, José Augusto (ENGOV, 2021)
The text argues that there has existed and will continue to exist for much time enough geographical space and related natural resources in the Brazilian national territory to accommodate the expansion of five sets of uses and activities: (i) rural productive activities, (ii) infra-structure installations, (iii) protected areas, and (iv) indigenous homelands and (v) maroon homelands. This point has become highly relevant because recently a pro-agriculture social coalition / lobby and an associated congressional caucus have argued that the expansion of Brazilian agricultural activities has been confined by protected areas and indigenous homelands. These actors call explicitly for the unfettered expansion of agricultural activities and consider it to be strategic for the future of Brazil as a major producer of food and agricultural commodities. This coalition gives little attention to the fact that rural activities compete for territory with other activities and land uses that are common components of modern societies and economies. The present text criticizes an influential research report that defends the unlimited expansion of agricultural activities. It also pulls together data that show the contrary – agricultural areas have expanded strongly over the last decades, the same having happened with areas dedicated to environmental protection, indigenous homelands and infrastructure installations. The major inference is that although agriculture may call for freedom to expand to “new frontiers”, it can also expand by improving the productivity in currently occupied lands and by using lands officially classified as underused, unused or abandoned by farmers. Additionally, it is argued that this pro-agriculture stance should not be rejected outright, but incorporated into a wider debate about a socially legitimate distribution of different land uses in the large, tropical, humid, biologically rich territory of Brazil.